Omics-based insights into therapy failure of pediatric B-lineage acute lymphoblastic leukemia - Suliman A. Alsagaby (Oncology Reviews, 2019)
B-lineage acute lymphoblastic leukemia (B-ALL) is the most common type of cancer seen in children and is characterized by a variable clinical course. Although there have been remarkable improvements in the therapy outcomes of pediatric B-ALL, treatment failure remains the leading-cause of death in 18% of the afflicted patients during the first 5 years after diagnosis. Molecular heterogeneities of pediatric B-ALL play important roles as determinants of the therapy response. Therefore, many of these molecular abnormalities have an established prognostic value in the disease. The present review discusses the omics-based revelations from epigenomics, genomics, transcriptomics and proteomics about treatment failure in pediatric B-ALL. Next it highlights the promise of the molecular aberration-targeted therapy to improve the treatment outcomes.